The effects of external ankle support on dynamic restraint characteristics of the ankle in volleyball players - Midgley, W.; Hopkins, J. T.; Feland, B.; Kaiser, D.; Merrill, G.; Hunter, I. (Clinical Journal of Sport Medicine, 2007)
Objective: To examine any changes in electromechanical delay and reaction time as a result of the use of external ankle supports over an entire season (3-5 months) in college volleyball players.